Gibbalaria : A new genus of Olethreutini from the Afrotropical Region (Lepidoptera: Tortricidae: Olethreutinae), and a new combination in Cosmopoda Diakonoff - Brown, John W.; Aarvik, Leif; Timm, Alicia (Zootaxa, 2023)
Gibbalaria Brown and Aarvik, new genus, is described to accommodate the following species: G. divergana Brown and Aarvik, new species (TL: South Africa); G. occidentana Brown and Aarvik, new species (TL: South Africa); G. chiloanei Brown and Aarvik, new species (TL: South Africa); G. scabellana Zeller, 1852, new combination (TL: South Africa); G. mabalingwae Razowski, 2008, status revised, new combination (TL: South Africa); G. longiphallus Brown and Aarvik, new species (TL: South Africa); G. bagamoyo (Razowski & Wojtusiak, 2014), new combination (TL: Tanzania); and G. analcis (Razowski, 2015), new combination (TL: Republic of Cameroon). Gibbalaria sistrata (Meyrick, 1911), new combination (TL: South Africa), is synonymized with G. scabellana, new synonymy. Although the male genitalia of Gibbalaria form two moderately divergent groups, the two groups share extremely similar female genitalia, which feature a broad, somewhat cylindrical antrum, followed immediately anterad by a conspicuously elbowed region of the ductus bursae forming a weak diverticulum on the left side, and a signum in the form of a patch of small arrowhead-shaped sclerites, usually with a shallow pocket. Male genitalia morphology shows many similarities with the Neopotamia group (Olethreutini), Afroploce Aarvik in particular. The monophyly of Gibbalaria is supported by the raised, curled, opalescent scales on the forewing in both sexes, which occurs in a few other genera scattered through the subfamily (e.g., Thylacandra Diakonoff in Grapholitini; Astronauta Diakonoff and Cosmopoda Diakonoff in Olethreutini); the angled diverticulum in the ductus bursae in the female genitalia; the subrectangular flange from the lower margin of the valva immediately basal to the cucullus; and the setose, protruding ridge immediate above the basal cavity, which appears to be homologous with the subbasal process of the valva in many members of the Neopotamia group of genera. In addition, Diakonoffiana graziani Razowski, 2015 (TL: Republic of Cameroon) is transferred to Cosmopoda Diakonoff, resulting in C. graziani (Razowski), new combination.